Double optical image encryption system based on near-field Fourier ptychography. Issue 11 (25th June 2022) - Chen, Linfei; Chen, Lei; Mao, Haidan
Abstract : This paper proposes a double encryption system based on near-field Fourier ptychography (FP). Firstly, the encryption and decryption processes of a complex-amplitude image are realized by the principle of near-field FP while improving the imaging system. Our method uses a spatial light modulator to apply a phase shift to the object in the frequency domain to control the displacement of the object in the spatial domain, avoiding systematic errors caused by mechanically moving object. The second encryption process is designed by further utilizing the characteristics of the imaging system and can recover the object and the illumination pattern at the same time, which can decrypt another image from the object and illumination pattern recovered above. Since the second encryption is harder to be detected by the attacker, it has higher concealment and security. Finally, numerical simulations verify the feasibility, security and robustness of the proposed encryption system.